Glycoconjugates Play a Key Role in Campylobacter jejuni Infection: Interactions between Host and Pathogen - Day, Christopher J.; Semchenko, Evgeny A.; Korolik, Victoria (Frontiers in Cellular and Infection Microbiology, 2012)
Glycan based interactions between host and pathogen are critical in many bacterial and viral diseases. Glycan interactions range from initial receptor based adherence to protecting the infective agent from the host’s immune response through molecular mimicry. Campylobacter jejuni is an ideal model for studying the role of glycans in host-pathogen interactions, as well as the role of bacterial surface glycoconjugates in infection. Using glycan array analysis, C. jejuni has been shown to interact with a wide range of host glycoconjugates. Mannose and sialic acid residues appear to play a role in initial interactions between host and pathogen following environmental exposure, whereas fucose and galactose based interactions are likely to be required for prolonged colonisation. Other studies have highlighted potential decoy receptor type interactions between host’s intestinal mucins and C. jejuni, demonstrating the importance of host glycoproteins as defence against C. jejuni infection as well as the role for glycoconjugates found in human breast milk in protection of breast feeding infants from infection with C. jejuni. C. jejuni can produce N- and O-linked glycoproteins, capsular polysaccharide (CPS) and/or lipooligosaccahride (LOS) which results in C. jejuni presenting its own diverse sugar coated displays on the cell surface. Bacterial glycans play an important and versatile role in infection and disease. Of these, the best understood is the molecular mimicry of human gangliosides presented by C. jejuni’s LOS and its link to the onset of autoimmune neuropathies such as the Guillain Barre Syndrome (GBS). However, the role of glycoconjugates presented by C. jejuni extends beyond expression of sialylated ganglioside structures involved in initiation of GBS. Expression of surface glycans by C. jejuni may also relate to the ability of this organism to interact with the glycoproteins for initial host-pathogen interactions and continued infectivity.